Retrospective study of livestock diseases registered at Government Veterinary Hospital in Shahjadpur upazila of Sirajganj district - Abu Huraira; Jahagir Alam; Tania Soltana; Md Mostafizur Rahman; Md Shakil Islam; Md Mominul Islam; Al Nur Md Iftekhar Rahman (Research in Agriculture Livestock and Fisheries, 2025)
The present study was undertaken to find out the suspected clinical diseases of livestock recorded in upazila veterinary hospital from October 1, 2021, to November 30, 2022. The data were collected from the registered book kept at the upazila livestock office and veterinary hospital and analyzed with standard methods. We found that cattle, sheep, and goats were frequently registered for treatment. Clinical diseases and conditions were diagnosed based on standard clinical and laboratory methods. We found that the percentage of tick infestation (18.19%), worm infestation (15.43%), non-specific fever (7.10%), mastitis (4.04%), coughing (2.69%), conjunctivitis (2.26%), dermatitis (2.21%), arthritis (1.59%) and babesiosis (1.92), diarrhea (17.73%), anorexia (8.75%), weakness (3.67%), bloat (2.08%), anestrus (4.77%), and naval ill (2.81%) in cattle. By contrast, the percentage of worm infestation (12.29%, coughing (11.61%), conjunctivitis (6.09%), non-specific fever (4.35%), PPR (3.87%), tick infestation (1.45%), diarrhea (32.52%), anorexia (15.10%), bloat (1.64%), weakness (1.06%), debility (1.06%) and anestrus (1.35%) were in goats. We also found that the percentage of worm infestation (16.66%), tick infestation (1.78%), coughing (16.39%), conjunctivitis (12.5%), non-specific fever (10.41%), rabies infection (1.48%), and peste des petits ruminants (1.19%), diarrhea (30.35%), anorexia (14.28%), and bloat (4.16%) were in sheep registered at upazila veterinary hospitals of Shahjadpur, Shirajganj. These findings will be crucial for the veterinary service provider and researcher to work together for the control and management of infectious and non-infectious diseases of livestock reared in rural areas of Bangladesh. Res. Agric. Livest. Fish. Vol. 11, No. 3, December 2024: 315-325